Weltneria acanthostoma sp. nov., a burrowing barnacle (Cirripedia: Acrothoracica) from the deep-waters of the South China Sea - Kolbasov, Gregory A.; Chan, Benny K.k.; Cheng, Yu-Rong (Zootaxa, 2017)
A new deep water acrothoracican species, Weltneria acanthostoma sp. nov., has been discovered from the area of the Blue Ridge Seamount, South China Sea, at a depth of 534 m. A single female was found in a burrow in the scleractinian Madrepora oculata. This specimen is assigned to the genus Weltneria due to the possession of six pairs of cirri and two-joined caudal appendages. Weltneria acanthostoma differs from its congeners in the morphology of the slightly sinusoid opercular bars having hooked posterior processes and four or five curved, conspicuous, simple teeth, and by the absence of a calcareous formation of the attachment disk. The genus Weltneria exhibits a Tethyan relictual pattern in its geographical distribution. The diagnosis of Weltneria is based on symplesiomorphies and the genus may be a non-monophyletic taxon.